2020
DOI: 10.1016/j.ecolecon.2020.106649
|View full text |Cite
|
Sign up to set email alerts
|

Regulation, governance and the role of the informal sector in influencing environmental quality?

Abstract: We investigate the effect of the informal sector and a range of governance indicators on both global and local pollutants for a panel of 58 countries during 1996-2011. The analysis employs a fixed effects-instrumental variable generalized method of moments approach. We find that the size of the informal sector has a significant impact on environmental quality, which is conditional on the level of economic development. For developing countries, the informal sector has a significant positive impact on local poll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(37 citation statements)
references
References 53 publications
3
28
0
Order By: Relevance
“…Recently, Omri and Ben Mabrouk (2020) show that good governance can be successful in rebalancing social, environmental, and economic components of sustainable developments for a panel of 20 economies in the MENA (Middle East and North Africa) region during the period 1996-2014. In a study of 58 selected economies covering the period 1996-2011 by Bali Swain et al (2020), it was confirmed that the degree of governance's impact relies essentially on the level of economic development, the pollutant type and the category of governance measure.…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…Recently, Omri and Ben Mabrouk (2020) show that good governance can be successful in rebalancing social, environmental, and economic components of sustainable developments for a panel of 20 economies in the MENA (Middle East and North Africa) region during the period 1996-2014. In a study of 58 selected economies covering the period 1996-2011 by Bali Swain et al (2020), it was confirmed that the degree of governance's impact relies essentially on the level of economic development, the pollutant type and the category of governance measure.…”
Section: Introductionmentioning
confidence: 94%
“…The EKC empirical evaluation has recognized that, in a reduced model, revenue serves as a proxy for too many other variables (e.g., economic structure, level of economic activity, etc. ), resulting in an omitted variables bias (Bali Swain et al, 2020). This awareness has brought about efforts to expand the model by incorporating pertinent variables related to economic structure, energy markets, trade openness, etc.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, the EKC empirical assessment found that revenue was a proxy for too many other variables in a reduced model (e.g., levels of activity, economic structure, etc. ), leading to a missing variable bias [16].…”
Section: Introductionmentioning
confidence: 99%
“…Second, the relevant literature studies the impact of environmental regulation on environmental issues at the national, regional and industry levels without considering environmental regulations at the corporate level, and the results may be in uenced by aggregated data (Ren et al 2018; Swain et al 2020;Levinson and Taylor 2004). This paper considers macro-environmental policy, RES and micro-enterprise environmental investment in the same scenario, not only to test the implementation effect of the central government policy from local governments but also to prove the effectiveness of environmental protection policy in terms of its effect on enterprises.…”
Section: Theoretical Contributionsmentioning
confidence: 99%